Ethical Leadership on Employee Performance Through Job Satisfaction as An Intervening Variable - Djaya, Yonatan Asadi; Muhammad Faaiz Pandu Dewanata; Rizky Maharani; Eisha Lataruva (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
This research attempts to investigate and evaluate how ethical leadership affects worker performance by using job satisfaction as a moderating factor for PT. X Employess. A quantitative research design was employed in this study. 112 respondents, or the whole population, were included in the study's sample. Questionnaires were distributed to each respondent as part of the data collection procedure. The impact of the research factors was then determined by testing, both directly and indirectly. According to the conclusions of the study, partially ethical leadership has no substantial impact on employee performance. Even yet, the path analysis's conclusions show that there is a relationship between ethical leadership and worker performance that is mediated by job satisfaction. Only 26.9% of cases showed that ethical leadership had an effect on employee performance based on job satisfaction measurements. According to job satisfaction, ethical leadership influenced just 26.9% of employee performance; the remaining proportion was explained by other variables not covered in the study.